Ultra-short course, high-dose primaquine to prevent Plasmodium vivax infection following uncomplicated pediatric malaria: A randomized, open-label, non-inferiority trial of early versus delayed treatment - Sze-Ann Woon; Brioni R. Moore; Moses Laman; Paula Tesine; Lina Lorry; Bernadine Kasian; Phantica Yambo; Gumul Yadi; William Pomat; Kevin T. Batty; Sam Salman; Leanne J. Robinson; et al. (International Journal of Infectious Diseases, 2023)
Objectives: We aimed to assess safety, tolerability, and Plasmodium vivax relapse rates of ultra-short course (3.5 days) high-dose (1 mg/kg twice daily) primaquine (PQ) for uncomplicated malaria because of any Plasmodium species in children randomized to early- or delayed treatment. Methods: Children aged 0.5 to 12 years with normal glucose-6-phosphate-dehydrogenase (G6PD) activity were enrolled. After artemether-lumefantrine (AL) treatment, children were randomized to receive PQ immediately after (early) or 21 days later (delayed). Primary and secondary endpoints were the appearance of any P. vivax parasitemia within 42 or 84 days, respectively. A non-inferiority margin of 15% was applied (ACTRN12620000855921). Results: A total of 219 children were recruited, 70% with Plasmodium falciparum and 24% with P. vivax. Abdominal pain (3.7% vs 20.9%, P <0.0001) and vomiting (0.9% vs 9.1%, P = 0.01) were more common in the early group. At day 42, P. vivax parasitemia was observed in 14 (13.2%) and 8 (7.8%) in the early and delayed groups, respectively (difference, −5.4%; 95% confidence interval −13.7 to 2.8). At day 84, P. vivax parasitemia was observed in 36 (34.3%) and 17 (17.5%; difference −16.8%, −28.6 to −6.1). Conclusion: Ultra-short high-dose PQ was safe and tolerated without severe adverse events. Early treatment was non-inferior to delayed treatment in preventing P. vivax infection at day 42.